The Impact of Expatriates’ Cross-Cultural Adjustment on Work Stress and Job Involvement in the High-Tech Industry - Chen, Min (Frontiers in Psychology, 2019)
The personal traits of expatriates influence their work performance in a subsidiary. Nevertheless, organizations tend to hire candidates who are suitable from the technological dimension but ignore personal and family factors. Expatriates might not be familiar with a foreign place, and most organizations do not provide so-called cultural adjustment training. The selected expatriates often accept the job without knowing the future prospects of their career, which can result in individual and family turmoil initially. Moreover, the unknown future career prospects and concern over when they will return to the parent company can affect expatriates’ work. Cross-cultural competence refers to the ability of individuals to work effectively and live normally in different cultural contexts, and this ability requires expatriate employees to adopt adaptive thinking patterns and behaviors in the host country. To explore the effect of expatriates’ cross-culture adjustment on their work stress and job involvement, this study therefore uses an empirical approach in which data are collected with a questionnaire survey and proposes specific suggestions, according to the results, to aid expatriates in their personal psychological adjustment. The results show that the challenges faced by expatriate employees are derived from assigned tasks, unknown environments, language barriers, and cultural differences. Excessive pressure will impose ideological and psychological burdens upon the expatriates and even lead to physical symptoms; however, the appropriate amount of pressure can play a driving role and promote the smooth progress of the work. High-tech industry employees who can adapt to the customs and cultures of foreign countries have higher work participation and are more likely to find ways to alleviate work stress. It has also been found that the stronger the cross-cultural competence of employees is, the better their adjustment to the host country and the higher their corresponding job performance.